Body fat responses to a 1-year combined exercise training program in male coronary artery disease patients - Pimenta, Nuno (2013)
Objective: To analyze the body fat (BF) content and distribution modifications in coronary artery disease (CAD) patients in response to a 1-year combined aerobic and resistance exercise training (CET) program. Design and Methods: We followed two groups of CAD male patients for 12 months. One group consisted of 17 subjects (57 6 12 years) who engaged in a CET program (CET group) and the other was a age-matched control group of 10 subjects (58 6 11 years). BF content and distribution were measured through dual energy X-ray absorptiometry (DXA) at baseline and follow-up. Results: We found no differences on body mass and BMI between baseline and end of follow-up in both groups but, in CET group, we found significant reductions in all analyzed BF depots, including total BF (21.60 6 6.00 vs. 20.32 6 5.89 kg, P < 0.01), % total BF (27.8 6 5.5 vs. 26.4 6 5.4%, P < 0.05), trunk fat (12.54 6 3.99 vs. 11.77 6 4.01 kg, P < 0.05), % trunk fat (31.1 6 6.9 and 29.2 6 7.1%, P < 0.05), appendicular fat (8.22 6 2.08 vs. 7.72 6 2.037 kg, P < 0.01), % appendicular fat (25.7 6 4.9 and 24.5 6 4.9%, P < 0.05), and abdominal fat (2.95 6 1.06 vs. 2.75 6 1.10 kg, P < 0.05). Control group showed significant increase in appendicular fat (7.63 6 1.92 vs. 8.10 6 2.12 kg, P < 0.05). Conclusions: These results confirm the positive effect of CET on body composition of CAD patients, despite no changes in body mass or BMI. In this study, we observed no alterations on BF distribution meaning similar rate of fat loss in all analyzed BF depots. These results also alert for the limitations of BMI for tracking body composition changes.